The determinants factors that affect purchase intention of counterfeit: a study of economic benefit counterfeit, hedonic benefit counterfeit and materialism predictors / Nuarain Anwar - Anwar, Nuarain (2022)
The purpose of this research is to study on purchase intention towards counterfeits. According to this study, the researcher can know how economic, hedonic and materialism affects the purchase intention towards counterfeit. In this research, counterfeiting is the trade of illegally made products that are manufactured in a way that resembles genuine goods, yet are inferior in terms of economic, hedonic and materialism. This research data was collected at higher institution level in Sungai Petani, Kedah. The researcher used questionnaire as an instrument to collect data for obtaining result in this research. One of the independent variables which is materialism are not significant towards the dependent variables and the hypothesis are being rejected but others independent variables are significant and can be accepted. The other of independent variables have strong relationship with the purchase intention towards counterfeit because the results are significant and can be accepted. Therefore, the original manufacturer should quick responds to the customer to make customer knows how to differentiate between the original products and counterfeit products so that customer will make a good purchase intention by purchasing the original products.